Pendekatan Pedagogis dalam Pengajaran Menulis Bahasa Indonesia: Telaah Literatur Empiris dan Teoretis - Anita Candra Dewi (FKIP UNSULTRA, 2025)
Writing is a complex language skill that requires an appropriate pedagogical approach in its teaching. This study aims to examine in depth the various pedagogical approaches used in teaching Indonesian writing, based on empirical and theoretical literature. A literature search was conducted of various indexed national and international journals published between. The study results indicate that five main pedagogical approaches are predominantly used: the process approach, the genre approach, the thematic-integrative approach, the contextual approach, and the technology-based approach. Each approach has advantages in improving specific aspects of students' writing skills, from idea development and text structure to increasing creativity and language accuracy. This study also highlights the importance of integrating pedagogical theory with learner needs in classroom practice. By understanding the characteristics and effectiveness of each approach, teachers can adapt strategies appropriate to the learning context and student needs. This study is expected to serve as a reference in curriculum development and learning strategies, as well as improving the competence of Indonesian language teachers in teaching writing skills more effectively and sustainably.